Effects of microencapsulated probiotics and plant extract on antioxidant ability, immune status and caecal microflora in Escherichia coli K88-challenged broiler chickens. Issue 1 (1st January 2019) - Dong, Z. L.; Wang, Y. W.; Song, D.; Wang, W. W.; Liu, K. B.; Wang, L.; Li, A. K.
ABSTRACT: In this study, a total of 180 one-day-old male Arbor Acres broilers were randomly allotted to 5 groups with 6 replicates per group. Birds in negative control group were fed a corn-soybean meal-based diet, and birds in positive control group, MEF group, COSE group, MEF + COSE group were challenged with E. coli K88 and supplemented with 0, 1 × 10 10 cfu MEF/kg of diets, 500 mg COSE/kg of diets or their combinations, respectively. Results showed that PC group had lower average body weight and greater E. coli counts in caecal contents than NC group. MEF and COSE significantly increased average body weight, serum IgA level, T-SOD activity compared with that of PC group. MEF and MIX group had less caecal E. coli counts than PC birds. The results indicated dietary supplementation of MEF and COSE had a positive moderating effect on E. coli K88-challenged broiler chickens.